Measurement of the W boson mass with the collider detector at Fermilab - Affolder, T; Akimoto, H; Akopian, A; Albrow, MG; Amaral, P; Amendolia, SR; Amidei, D; Anikeev, K; Antos, J; Apollinari, G; Arisawa, T; Asakawa, T; et al. (2001)
We present a measurement of the W boson mass using data collected with the CDF detector during the 1994-1995 collider run at the Fermilab Tevatron. A fit to the transverse mass spectrum of a sample of 30115 W → ev events recorded in an integrated luminosity of 84 pb-1 gives a mass MW=80.473±0.065(stat) ±0.092(syst) GeV/c2. A fit to the transverse mass spectrum of a sample of 14740 W → μν events from 80 pb-1 gives a mass MW=80.465±0.100(stat)±0.103(syst) GeV/c2. The dominant contributions to the systematic uncertainties are the uncertainties in the electron energy scale and the muon momentum scale, 0.075 GeV/c2 and 0.085 GeV/c2, respectively. The combined value for the electron and muon channel is MW=80.470±0.089 GeV/c2. When combined with previously published CDF measurements, we obtain MW=80.433±0.079GeV/c2. ©2001 The American Physical Society.